(1-secx)/(1-cosx)=-secx

Please explain each step.

(1-secx)/(1-cosx)=-secx(1-(1/cosx))/(1-cosx)=1/cosx((cosx-1)/(cosx))/(1-cosx)=-secx-secx(1-cosx)=((cosx-1)/(cosx))-(1/cosx)(1-cosx)=((cosx-1)/(cosx))(1/cosx)(cosx-1)=((cosx-1)(1/(cosx))(1/cosx)=(1/(cosx))Therefore left side equals right side.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up